Strategies for the treatment of Hepatitis C in an era of interferon-free therapies: what public health outcomes do we value most?. Issue 11 (6th November 2014) - Innes, Hamish; Goldberg, David; Dillon, John; Hutchinson, Sharon J
Abstract : Objective: The expense of new therapies for HCV infection may force health systems to prioritise the treatment of certain patient groups over others. Our objective was to forecast the population impact of possible prioritisation strategies for the resource-rich setting of Scotland. Design: We created a dynamic Markov simulation model to reflect the HCV-infected population in Scotland. We determined trends in key outcomes (e.g. incident cases of chronic infection and severe liver morbidity (SLM)) until the year 2030, according to treatment strategies involving prioritising, either: (A) persons with moderate/advanced fibrosis or (B) persons who inject drugs (PWID). Results: Continuing to treat the same number of patients with the same characteristics will give rise to a fall in incident infection (from 600 cases in 2015 to 440 in 2030) and a fall in SLM (from 195 cases in 2015 to 145 in 2030). Doubling treatment-uptake and prioritising PWID will reduce incident infection to negligible levels (<50 cases per year) by 2025, while SLM will stabilise (at 70–75 cases per year) in 2028. Alternatively, doubling the number of patients treated, but, instead, prioritising persons with moderate/advanced fibrosis will reduce incident infection less favourably (only to 280 cases in 2030), but SLM will stabilise by 2023 (i.e. earlier than any competing strategy). Conclusions: Prioritising treatment uptake among PWID will substantially impact incident transmission, however, this approach foregoes the optimal impact on SLM. Conversely, targeting those with moderate/advanced fibrosis has the greatest impact on SLM but is suboptimal in terms of averting incident infection.